TINGKAT UMUR, PARITAS DAN PENGETAHUAN IBU TENTANG PEMERIKSAAN IVA SEBAGAI DETEKSI DINI KANKER LEHER RAHIM - endang buda setyowati (Akademi Kebidanan Griya Husada Surabaya, 2016)
ABSTRACTIntroduction IVA examination is a cervical cancer screening examination by Visual Inspection with Acetic Acid (IVA). The achievement of IVA examination at Manukan Kulon Community Health Center is still below the target every month (20% of KB acceptors). From the preliminary study of the majority of mothers aged <20 years who have not had an IVA examination, most of them are grandemultipara and lack knowledge. This study aims to analyze how the description of age, parity and knowledge of mothers about IVA examination as early detection of cervical cancer at Manukan Kulon Health Center in May 2015. Method: The research design used was descriptive research. The sample used was 65 KB acceptors in May 2015. Sampling is done on a non probability sampling by using saturated sampling, where the total population is sampled. Data collection uses primary data, then tabulated frequency and cross tabulation. Results: Based on the research that has been done, the results show that the majority of age> 35 years (44.62%), grandemultipara parity (41.54%) and less knowledgeable (49.23%). The results of the majority of cross tabulations that carried out IVA examinations were 20-35 years old (33.33%), grandemultipara parity (25.93%) and good knowledge (50%) compared to those who did not have an IVA examination <20 years old, primiparous and knowledgeable parity less (93.75%). Discussion: Based on the results of the study it was concluded that age, parity and knowledge influence the IVA examination. Therefore it is necessary to have innovative steps such as socialization of IVA in the community and in the effort of early detection of cervical cancer IVA checks must be carried out regularly.